2015
DOI: 10.1104/pp.15.00182
|View full text |Cite
|
Sign up to set email alerts
|

Mutant Allele-Specific Uncoupling of PENETRATION3 Functions Reveals Engagement of the ATP-Binding Cassette Transporter in Distinct Tryptophan Metabolic Pathways

Abstract: Arabidopsis (Arabidopsis thaliana) PENETRATION (PEN) genes quantitatively contribute to the execution of different forms of plant immunity upon challenge with diverse leaf pathogens. PEN3 encodes a plasma membrane-resident pleiotropic drug resistance-type ATP-binding cassette transporter and is thought to act in a pathogen-inducible and PEN2 myrosinasedependent metabolic pathway in extracellular defense. This metabolic pathway directs the intracellular biosynthesis and activation of tryptophan-derived indole g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 66 publications
5
88
0
1
Order By: Relevance
“…Two different classes of such chemicals may be involved in this process: surface-coating materials, as shown for AtABCG32/PEC1 (21,22), and secondary metabolites, as shown for AtABCG36/PDR8/ PEN3 (14). We tested the first possibility by an ethanol penetration assay that detects permeability defects but could not observe any difference in ethanol penetration between the wildtype plants and atabcg34 mutants (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two different classes of such chemicals may be involved in this process: surface-coating materials, as shown for AtABCG32/PEC1 (21,22), and secondary metabolites, as shown for AtABCG36/PDR8/ PEN3 (14). We tested the first possibility by an ethanol penetration assay that detects permeability defects but could not observe any difference in ethanol penetration between the wildtype plants and atabcg34 mutants (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PDR8/ ABCG36/PEN3, which is localized at the plasma membrane, recruited to infection sites (11), and involved in glucosinolatedependent pathogen defense at the contact site (12), blocks the penetration of nonhost fungal pathogens (13). Recently, a report suggested that this protein transports 4-O-β-D-glucosyl-indol-3-yl formamide (4OGlcI3F) (14); however, this possibility remains to be proven. atabcg40/pdr12 mutants exhibit sensitivity to sclareol, and AtABCG40/PDR12 is induced by pathogen inoculation (15).…”
Section: Significancementioning
confidence: 99%
“…Together, these data support a scenario in which PEN3 mediates the ATP-dependent transport of glucosinolates that were enzymatically activated by PEN2 and are potentially toxic for invading pathogens (Stein et al, 2006). PEN2 was shown to hydrolyze indol-3-ylmethylglucosinolate (I3G) and 4-methoxyindol-3-ylmethylglucosinolate (4MI3G) (Bednarek et al, 2009) and to be required for production of 4-O-b-D-glucosylindol-3-yl formamide (Lu et al, 2015). Deglucosylated precursor molecules of the latter have recently been proposed to represent the critical PEN3 transport substrate in powdery mildew entry control (Lu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…PEN2 was shown to hydrolyze indol-3-ylmethylglucosinolate (I3G) and 4-methoxyindol-3-ylmethylglucosinolate (4MI3G) (Bednarek et al, 2009) and to be required for production of 4-O-b-D-glucosylindol-3-yl formamide (Lu et al, 2015). Deglucosylated precursor molecules of the latter have recently been proposed to represent the critical PEN3 transport substrate in powdery mildew entry control (Lu et al, 2015). As I3G and 4MI3G contain S-glycosidic bonds, PEN2 represents a thioglucosidase (myrosinase) but was designated as an atypical myrosinase due to an unusual amino acid composition within the catalytic center.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, 4-O-b-D-glucosyl-indol-3-yl formamide was identified as a pathogen-inducible, tryptophan-derived compound whose biosynthesis is dependent on an intact PEN2 metabolic pathway. Based on the overaccumulation of 4-O-b-Dglucosyl-indol-3-yl formamide in the leaf tissues of pen3 mutants, it was proposed that its precursor is the cargo of PEN3, an ATP binding cassette transporter, in extracellular pathogen defense (Lu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%